2021
DOI: 10.1186/s13722-021-00266-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of methamphetamine/amphetamine use on receipt and outcomes of medications for opioid use disorder: a systematic review

Abstract: Background Methamphetamine/amphetamine use has sharply increased among people with opioid use disorder (OUD). It is therefore important to understand whether and how use of these substances may impact receipt of, and outcomes associated with, medications for OUD (MOUD). This systematic review identified studies that examined associations between methamphetamine/amphetamine use or use disorder and 3 classes of outcomes: (1) receipt of MOUD, (2) retention in MOUD, and (3) opioid abstinence during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 78 publications
8
32
0
2
Order By: Relevance
“…However, there was no statistically significant change in self-reported or biologically confirmed stimulant use from baseline to 90 days among PWH or participants without HIV following initiation of MOUD. Previous studies of the effect of MOUD on stimulant use are conflicting, with some evidence that higher-dose buprenorphine (16 mg) may reduce cocaine use [ 39 ], while it has also been found that persons who use methamphetamine or amphetamine may have lower opioid abstinence and receipt of or retention on MOUD [ 21 ]. In our cohort, methamphetamine use was very low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no statistically significant change in self-reported or biologically confirmed stimulant use from baseline to 90 days among PWH or participants without HIV following initiation of MOUD. Previous studies of the effect of MOUD on stimulant use are conflicting, with some evidence that higher-dose buprenorphine (16 mg) may reduce cocaine use [ 39 ], while it has also been found that persons who use methamphetamine or amphetamine may have lower opioid abstinence and receipt of or retention on MOUD [ 21 ]. In our cohort, methamphetamine use was very low.…”
Section: Discussionmentioning
confidence: 99%
“…Medications for opioid use disorder (MOUD; eg, buprenorphine, methadone, and extended-release naltrexone) are an evidence-based strategy to address opioid addiction and are associated with reduced opioid IDU [ 14–20 ]. However, MOUD retention and opioid abstinence may be affected by co-stimulant use [ 21 ]. For PWID, MOUD is also associated with increased self-reported retention and uptake of DAA treatment; however, the HCV cascade of care highlights important gaps [ 22 ], and successful HCV treatment strategies involve a multidisciplinary effort in care coordination and case management, particularly for those with psychiatric illness or substance use disorder [ 23 , 24 ].…”
mentioning
confidence: 99%
“…The clinical data suggest that there has been a substantial increase in concomitant opioid and methamphetamine use (17,25,31), and mainly these two substances have led to a twin epidemic in the United States (16,31). Addiction specialists have begun to encounter increasing methamphetamine use in patients with opioid use disorder and the complicated clinical features, such as treatment nonadherence (36), injecting substance use (23), and associated risks such as viral hepatitis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found amphetamine and polysubstance use were more common in the DRA-OPAT participants who did not complete IV antibiotic treatment, although the impact of specific substance used on completion of therapy could not be determined due to inadequate sample size. Recent data suggest methamphetamine use adversely affects MOUD receipt, retention, and opioid abstinence in patients with opioid use disorder [ 14 ].…”
Section: Discussionmentioning
confidence: 99%